2018
DOI: 10.1038/s41598-018-20389-y
|View full text |Cite
|
Sign up to set email alerts
|

First in situ evidence of wakes in the far field behind offshore wind farms

Abstract: More than 12 GW of offshore wind turbines are currently in operation in European waters. To optimise the use of the marine areas, wind farms are typically clustered in units of several hundred turbines. Understanding wakes of wind farms, which is the region of momentum and energy deficit downwind, is important for optimising the wind farm layouts and operation to minimize costs. While in most weather situations (unstable atmospheric stratification), the wakes of wind turbines are only a local effect within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
153
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 215 publications
(200 citation statements)
references
References 50 publications
10
153
1
1
Order By: Relevance
“…Christiansen and Hasager (2005) observed offshore wakes via sythetic aperture radar satellite images and showed that these wakes can propagate 20 km downwind. These results were confirmed, recently, by airborne measurements taken downwind of large offshore wind farms at the North Sea (Platis et al 2018). During stable atmospheric conditions, these offshore wakes can be longer than 70 km at offshore sites (Platis et al 2018).…”
Section: Introductionsupporting
confidence: 62%
“…Christiansen and Hasager (2005) observed offshore wakes via sythetic aperture radar satellite images and showed that these wakes can propagate 20 km downwind. These results were confirmed, recently, by airborne measurements taken downwind of large offshore wind farms at the North Sea (Platis et al 2018). During stable atmospheric conditions, these offshore wakes can be longer than 70 km at offshore sites (Platis et al 2018).…”
Section: Introductionsupporting
confidence: 62%
“…Offshore wind power plant wakes can extend tens of km downwind (Platis et al, ; Siedersleben, Platis, et al, ; Siedersleben, Lundquist et al, ) in low‐turbulence, stably stratified conditions. These wakes undermine offshore power production (Nygaard, ).…”
Section: Discussionmentioning
confidence: 99%
“…Offshore ϵ has, on average, smaller values compared to those found in comparable studies onshore, with a weak diurnal cycle. The small average values of ϵ are conducive to strong and long‐lived wakes such as wakes observed in stable stratification in the North Sea (Platis et al, ; Siedersleben, Lundquist et al, ; Siedersleben, Platis, et al, ). Moreover, this extended persistence of wakes will occur throughout the diurnal cycle, given the absence of strong turbulence dissipation even in convective daytime conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SAR wind maps contribute with information about the far-wake field, which is typically not available from other sources. Recently, the first airborne in situ measurements of the far-wake field became available showing that wind farm wakes frequently extend over several tens of kilometres (Platis et al, 2018).…”
Section: Introductionmentioning
confidence: 99%